3x^2 + 6 - 2x + 5x - 4x^2 + 9A. -x^2 + 3x + 15
B. 7x^2 + 3x + 3
C. x^2 - 3x + 15
D. -x^2 7x + 15

Answers

Answer 1
Answer: Hello,

I suppose you want to reduce the expression:

Answer A

3x²-4x²-2x+5x+6+9=-2x²+3x-15


Related Questions

A person's temperature is 40° C. What would it be in Kelvin? A. −313 K B. 313° C C. 313 K D. −313° C
What is -4 x 3 when 4 is negative??
a test has 25 questions and is worth a total of 100 points. it consists of multiple choice that are worth 8 points each and short answer that are worth 3 points each. how many multiple choice are there on the test?
If a coin is flipped 75 times, in how many ways could there be exactly two tails?
The population of Florida in 2010 was 18,801,310 and the land area was 53,625 square miles. The population increased 5.8% by 2014. To the nearest whole number what is the population density in people per square mile for Florida in 2014? To the nearest whole number how much did the population density in people per square mile increase from 2010 to 2014?

of the400 doctors who attended a conference, 240 practiced family medicine and 130 were from countries outside the United States. One-third of the family medicine practitioners were not fem the united states....WHATS IS THE PROBABILITY A DOCTOR PRACTICE FAMILY MEDICINE OR IS FROM THE UNITED STATES?

Answers

3/5 were there for family med
27/40 of all were from us
2/5 were both from us and studied family med
Srry if its too late or not what u needed

Answer:539i think I am not sure

Step-by-step explanation:

Four less than the product of a number and 7 is eight more than that number

Answers

Let the number be x, then 7x - 4 = x + 8
7x - x = 8 + 4
6x = 12
x = 12/6 = 2.

Therefore, the number is 2.

Solve mathematics problem in photo please!

Answers

Hello,

8/(x-7)=7/2
==>(x-7)*7=8*2
==>7x-49=16
==>7x=65
==> x =9+2/7

Answser A

The binomial expression (x+2) (x+3) can be rewritten by using the distributive laws as x(x+3) + 2(x-3)x(x+2) - 3(x+2)
x(x+3) + 2(x+3)
x(x+3) + 2(x+3)

Answers

Answer:

my answer is x(x+3) + 2(x - 3)

Answer:

thanks for the information

Step-by-step explanation:

A baseball team plays in a stadium that holds 50000 spectators. When the ticket price is $10, the average attendance is 27000. When the price is lowered to $6, the average attendance rose to 39000. Find a demand function, D(q), where q is the quantity or number of spectators and D(q) is linear.

Answers

Answer:

the answer is below

Step-by-step explanation:

Demand seems to be based on price.

Therefore we must consider two things:

that "x" is equal to the price and that "y" is equal to the average attendance.

Thus:

the two points would be:

(x1, y1) = (10,27000)

(x2, y2) = (6.39000)

The slope of a straight line is given by:

m = (y2-y1) / (x2-x1)

we replace:

m = (39000 - 27000) / (6 - 10) = 12000 / -4 = -3000

The equation of a straight line can be expressed like this

y = m * x + b.

where

m is the slope and b is the y-intercept.

we replace

y = -3000 * x + b.

To solve for b, replace x and y with the value of one of the points on the line.

We choose (6.39000). and we replace:

39000 = -3000 * 6 + b

39000 = -18000 + b

39000 + 18000 = b

b = 57000.

if we replace we have:

the equation becomes y = -3000 * x + 57000

since it is the demand and * x is the price.

t = d (x), therefore the equation becomes

d (x) = -3000 * x + 57000.

d (x) = 57000 - 3000 * x.

when x = 0, the price is 0 and the demand will be 57000, which will be more than the stadium can contain because the stadium can only contain 50,000.

So:

when x = 6, the price is 6 and the demand is 57000 - 18000 = 39000.

when x = 10, the price is 10 and the demand is 57000 - 30000 = 27000.

Final Answer:

The demand function D(q) we are looking for is given by D(q) = -3q + 351,000.

Explanation:

We're looking for a linear demand function D(q) of the form D(q) = aq + b, where q is the quantity or number of spectators.

We have two pieces of information here:

1) When the ticket price is $10, the average attendance is 27000, which gives us the equation: 10 * 27000 = a * 27000 + b, i.e 270,000 = 27,000a + b.

2) When ticket price is lowered to $6, the average attendance rose to 39000, which gives us the equation: 6 * 39000 = a * 39000 + b, i.e  234,000 = 39,000a + b.

Let's solve this system of equations to find the values of a and b.

To isolate a, we can subtract the second equation from the first: 270,000 - 234,000 = 27,000a - 39,000a, this simplifies the equation to 36,000 = 12,000a.

So, we divide both sides by 12,000 to solve for a:

a = (270,000 - 234,000) / (27,000 - 39,000) = -3.

So, the coefficient of q in our demand function is -3.

Now, let's find b by plugging in the value of a into the first equation.

Thus, b is equal to 270,000 - (27,000 * -3), which gives

b = 270,000 + 81,000 = 351,000.

At this point, we have the values for our coefficients a and b as -3 and 351,000, respectively.

Therefore, the demand function D(q) we are looking for is given by D(q) = -3q + 351,000.

To know more about demand function:

brainly.com/question/38859172?

#SPJ12

What does the product of any whole-number factor multiplied by 100 always have ? Explain

Answers

The product of any whole number factor multiplied by 100 basically is just the number with an extra two zeros on the end. This is the case with any whole number.

Examples:
13 x 100 = 1300
444 x 100 = 44400
7 x 100 = 700